A primer on chiefs and chiefdoms - Earle, Timothy K., 1946- (Eliot Werner Publications, Incorporated, 2021)
"Chiefdoms are traditional societies that are relevant for our modern world. The author argues that studying chiefdoms is essential to understanding the role of elemental powers in social evolution. As an illustration, he studies chiefs and their power strategies in historically independent prehistoric and traditional societies and discusses how they continue to exist as powerful actors within states. Chiefs are political operatives who hold titles of leadership over groups larger than intimate kin-based communities. Although they rule with the consent of their group, they are all about building personal power and respect. Many scholars have viewed chiefs as problem solvers-defending groups against aggressors, resolving disputes, providing support under hardship, organizing labor for community projects, and redistributing goods among those in need. Chiefs do these things, but much of what chiefs do is to accumulate benefits for themselves, staying in power and legitimizing control. Anthropological archaeology is well suited to pursue the study of chiefdoms, their leadership institutions, and long-term historical processes more generally"-- Provided by publisher.
Keywords: Chiefdoms -- History.; Human evolution.; Economics -- Political aspects.; Chefferie (Anthropologie) -- Histoire.; Êtres humains -- Évolution.; Économie politique et politique.; POLITICAL SCIENCE / History & Theory; Chiefdoms; Economics -- Political aspects; Human evolution; History